Aktivitas Anti-Inflamasi Senyawa Squale dari Ekstrak Metanol Abroma augusta L pada Mus musculus - Latief, Madyawati; Muhaimin, Muhaimin; Amanda, Hilda; Prahandika, Graha; Tarigan, Indra Lasmana (POLTEKKES KEMENKES YOGYAKARTA, 2020)
Abroma augusta L plant traditionally was used to treat swellings, cuts, sores, and bruises. In the province of Jambi, A. augusta is used in folk medicine to treat wounds. This study aims to isolate the steroid compound from the root of A. augusta L and determine its anti-inflammatory activities. Extraction and fractionation have been done with graded maceration using solvents with different polarities, which are n-hexane, ethyl acetate, and methanol. The separation was performed by column chromatography, followed by preparative thin-layer chromatography. The characterization of the isolate was carried out using UV-Vis spectrophotometry and infrared spectrophotometry, GC-MS. The anti-inflammatory activities of methanol extract and isolate of A. augusta was performed in this study was designed to evaluate the dose-response relationship of the anti-inflammatory activity in rat models of chronic inflammation chromatography to obtain isolate 2.1.1 that characterize and showed maximum absorbance at 265. The result of IR showed the presence of functional groups, -C=C-H, -C=H, -CH, CH3, CH2, and –CO belongs to the steroid compound. The results of the GC-MS show that isolates contain squalene compounds with a value of m/z 410, Isolate and crude extract showed an anti-inflammatory activity that almost approached the positive control of sodium 4-chlorophenolate. It could be concluded that isolate and extract provide good anti-inflammatory activity, that promise for new drug candidate squalene-based A. augusta.